2010
DOI: 10.1016/j.cmet.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Signaling in Forebrain and Sympathetic Neurons Is a Key Determinant of Endocannabinoid Actions on Energy Balance

Abstract: The endocannabinoid system (ECS) plays a critical role in obesity development. The pharmacological blockade of cannabinoid receptor type 1 (CB(1)) has been shown to reduce body weight and to alleviate obesity-related metabolic disorders. An unsolved question is at which anatomical level CB(1) modulates energy balance and the mechanisms involved in its action. Here, we demonstrate that CB(1) receptors expressed in forebrain and sympathetic neurons play a key role in the pathophysiological development of diet-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
180
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(195 citation statements)
references
References 32 publications
11
180
1
3
Order By: Relevance
“…Interestingly, we found that androgenic decreased (DT) negatively, while estrogenic increased (DE 2 ) positively, correlated with the number of MetS components. The existence of correlations between sex hormone levels and body fat distribution could also be envisaged but not demonstrated in this study because of the technical difficulties in applying to rabbits the micro-CT system used with small rodents (Quarta et al 2010). Moreover, testosterone dosing in HFD rabbits improved insulin sensitivity (reduction of glycemia, improvement of glucose tolerance, and reduction of VAT).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we found that androgenic decreased (DT) negatively, while estrogenic increased (DE 2 ) positively, correlated with the number of MetS components. The existence of correlations between sex hormone levels and body fat distribution could also be envisaged but not demonstrated in this study because of the technical difficulties in applying to rabbits the micro-CT system used with small rodents (Quarta et al 2010). Moreover, testosterone dosing in HFD rabbits improved insulin sensitivity (reduction of glycemia, improvement of glucose tolerance, and reduction of VAT).…”
Section: Discussionmentioning
confidence: 98%
“…Energy expenditure enhanced by blockade of central CB1 antagonists is primarily mediated by sympathetic activation via central nervous system action. 6,7,31 In contrast to rimonabant, acute treatment with BPR697 did not elevate energy expenditure, which is well correlated with its poor central nervous system penetration. This result indicates the weight loss from BPR697 is not due to enhancement of energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the endocannabinoid system (ECS), which comprises the cannabinoid receptors, the endogenous ligands and the enzymes responsible for synthesis and degradation of endocannabinoids, is present in all strategic tissues controlling energy balance (Cota & Woods 2005) and it has been involved in the pathogenesis of obesity (Di Marzo et al 2009, Quarta et al 2010. Besides its important role in the hypothalamus and brain reward system in controlling food intake, elements of the ECS are also expressed in key peripheral tissues controlling metabolism, i.e.…”
Section: Introductionmentioning
confidence: 99%